Culture of Cyclops for Use the First Intermediate Host in Experimental life Cycle of SpirometraSpecies - Nicholas, Jairo Kavana (Journal of Veterinary Healthcare, 2021)
Background In natural conditions Cyclops are the first intermediate hosts in the life cycle of Spirometra species. In this paper we describe simple method of culturing Copepod of the genus Cyclops for use the first intermediate host in experimental life cycle of Spirometra species. Methods Paramecium was first cultured to be used as food for Cyclops. Sample of water was collected from a pond within Sokoine University. About 100 ml of water and pre-boiled wheat grains were transferred in a Petri dish and kept under laboratory conditions for 7 days, a swarm of Paramecium was formed. An adult female egg sacked Cyclops from a natural water pond in Tarangire National Park, Tanzania was added in a new Petri dish containing tap water, 0.3 ml of Paramecium suspension and 4 pre-boiled wheat grains. The mixture was kept under laboratory conditions temperature 26-29⁰C and observed daily. Results Eggs from the single Cyclops hatched to nauplius. The average time of developing to nauplius I was 1.2 days, nauplius I to copepodite I was 6.9 days, and copepodite I to adult female Cyclops was 26.3 days. The average measurements of naupliusI were 120.2µm length and 80.0µm width while the adult female was 846.3µm length and 284.6µm width. The adult female produced 1 to 8 broods (mean 4.3). The life span of Cyclops averaged 43.1 days. Conclusion The Cyclops cultured in the laboratory were fed Paramecium and used as first intermediate host in the experimental life cycle of Tanzanian Spirometra species.
Keywords: Cyclops; Paramecium; nauplius; Spirometra; culture